Monetary Policy, Informality and Business Cycle Fluctuations in a Developing Economy Vulnerable to External Shocks (The Pakistan Development Review, 2012)
Modelling the sources of Business Cycle Fluctuations (BCF)1 in an open economy Dynamic Stochastic General Equilibrium (DSGE) framework is a fascinating area of research. The main advantage of this framework over traditional modelling approach is due to an additional feature of micro-foundations in terms of welfare optimisation. This feature allows structural interpretation of deep parameters in a way that is less skeptical to Lucas critique [Lucas (1976)]. In DSGE modelling context, the sources of BCF are normally viewed as exogenous shocks, which have potential power to propagate the key endogenous variables within the system. This requires a careful identification, as the transmission of these shocks may emanate from internal side, such as, political instability; weak institutional quality in terms of low governance, or from external side, such as, natural disaster (like, earth quacks and floods); international oil and commodity prices; sudden stops in foreign capital inflows; changes in term of trade and exchange rate, or any combination of shocks from both sides. Also, the nature and magnitude of these shocks may vary, depending upon their variances and persistence levels.